Egyenlőtlen esélyek az iskolai képzésben: Az iskolázottsági esélyek változása az 1980-as évek végéig - Róbert, Péter (Szociológiai Szemle, 2024)
The paper studies the dependence of education, specifically the probabilities of reaching the various levels of education, on the social background of parents. The computer linked data base on 11.999 persons derives from three representative national surveys in the years 1986, 1988, and 1989. The data were processed separately for males and females in four cohorts born between 1923 and 1962, thus the paper covers the period from the early 1940s to the late 1980s. In its main lines, it repeats the analysis conducted by R. Andorka and A. Simkus on data of the year 1973. The methods applied are linear and logistic regression.The author finds that the dependence of education as such on social background m easured by the father’s occupation and education slightly decreases from the oldest cohort toward the youngest. The general rise in educational levels, a balancing of qualifications between males and females can also be clearly seen. And yet, when not education in general but the probabilities of reaching the successive levels of education are in the focus of analysis, a tangible improvement for both sexes can only be demonstrated in the саsе of primary education. Secondary education shows already a gender-specific duality: whereas men prefer training for skills, women choose the humanities and ’academic’ training. The probability of higher education, when compared to the number of high school graduates entitled to enrolment, shows a decreasing trend from the oldest cohort to the youngest. This is particularly true in the case of traditional university studies and for women.